Perceptions and Experiences of Women with Birth-related Perineal Injuries regarding Postpartum ‎Care: A Qualitative Exploration - Nahid Jahanishoorab; Ali Taghipour; Robab Latifnejad Roudsari (Mashhad University of Medical Sciences, 2022)
Background & aim: Birth-related perineal injuries, especially its severe degrees, could result in unpleasant childbirth experience and affect maternal and infant morbidities. Since, it is possible to improve the quality of care through understanding patients' expectations and experiences, this study was conducted to explore the perceptions and experiences of women with perineal injuries in postpartum care.Methods: In this qualitative study, 22 women with various degrees of perineal trauma were purposively selected between 10 days to one year after childbirth from hospitals and healthcare centers in Mashhad, Iran in 2016. Data collection was carried out through in-depth, face-to-face semi-structured interviews.  Data were concurrently analyzed through conventional content analysis using inductive approach of Elo and kyngas (2008) following data organization by MAXQDA software (version 10).Results: Postpartum care of women with severe perineal injuries was explained as "unethical practices in care" with two emerged categories including "lack of professional responsibility" comprising two subcategories of "short term follow-up" and "neglect of comprehensive care " as well as unethical communications" consisting of three subcategories of "dishonesty", "inactive listening", and "lack of compassion".Conclusion: Postpartum care in women with severe perineal trauma needs to be reviewed so that follow-up care and comprehensive provision of required services should be taken into account with focus on effective communication skills including honesty, active listening and compassion.